2016
DOI: 10.1200/jco.2015.65.9508
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutation Correlates With High-Risk Langerhans Cell Histiocytosis and Increased Resistance to First-Line Therapy

Abstract: International audiencePurpose Langerhans cell histiocytosis (LCH) is an inflammatory myeloid neoplasia with a broad spectrum of clinical manifestations and outcomes in children. The somatic BRAFV600E mutation occurs frequently, but clinical significance remains to be determined. Patients and Methods BRAFV600E mutation was investigated in a French LCH cohort. We analyzed associations between mutation status and clinical presentation, extent of disease, reactivation rate, response to therapy, and long-term perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
244
6
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(289 citation statements)
references
References 31 publications
12
244
6
10
Order By: Relevance
“…In children with LCH, the BRAF V600E mutation is associated with an increased risk of recurrence in systemic LCH, a high-risk disease (with risk organs) with increased resistance to first-line therapy [76,83].…”
Section: Pathogenesismentioning
confidence: 99%
“…In children with LCH, the BRAF V600E mutation is associated with an increased risk of recurrence in systemic LCH, a high-risk disease (with risk organs) with increased resistance to first-line therapy [76,83].…”
Section: Pathogenesismentioning
confidence: 99%
“…Basing on extrapolated observations made during randomised trials in children, various types of cytoreductive therapy (methotrexate, vinblastine, 6 mercaptopurine, etoposide) have been applied in adult LCH patients [3,[42][43][44][45][46][47][48][49]. However, the disease in adults runs a diverse clinical course and many drugs are differently tolerated.…”
Section: Chemotherapymentioning
confidence: 99%
“…The researches conducted among French LCH children have shown that detection of BRAF mutation was associated with a weaker response not only to the first-line treatment (vinblastine and steroids) but also a weaker response to a second-line treatment and a higher proportion of recurrence [16,19,49].…”
Section: Vemurafenib and Other Braf Inhibitorsmentioning
confidence: 99%
“…Howarth et al reported that among all the patients with bone lesions included in their study, the most frequent osseous invasion sites were the skull (29.9%), proximal femur (12.4%), and ribs (11.1%) (7). Conversely, only 2/314 cases (0.6%) invaded the sternum; other involved organs included the skin (36.9-39%), lymph nodes (19%), liver (16%), spleen (13%), oral mucosa (13%), lung (10-14%), and central nervous system (6-16%) (7)(8)(9). Other symptoms of LCH reported were relatively nonspecific, including dyspnea (14%), malaise, painful scalp lump (9%), spontaneous pneumothorax (7%), and/or diabetes insipidus (6%) (7).…”
Section: Case Presentationmentioning
confidence: 99%